Product Market Regulation and the Benefits of Wage Moderation - Estevão, Marcello M. (International Monetary Fund, 2005)
Euro-area real wages have decelerated sharply in the last 20 years, but this has not yet translated into visibly lower unemployment or faster growth. Weak output growth after such a cost shock is somewhat puzzling and has led some to question the benefits of wage moderation. By isolating structural from cyclical factors in a panel of industrial countries, I show that structurally slower real wage growth, that is, ""wage moderation,"" does raise output growth and lower unemployment rates. However, I show that the impact on both variables depends crucially on product market regulation: weaker competition and barriers to entry mute the growth effects of structural real wage changes by allowing incumbent firms to appropriate larger rents. In this context, overly regulated product markets in the euro area are undermining the effects of labor market reforms on output and employment